Medicinal Plants Used in the Treatment of Gastrointestinal Disorders in Rupandehi District, Western Nepal - Singh, Anant Gopal (Butwal Campus Journal, 2021)
Medicinal plants used for the cure of various diseases since time immemorial. The majority of population of developing countries also used traditional medicine because of poverty and no side effect. Ethnobotany survey was undertaken to collect information from traditional healers on the use of medicinal plants in the treatment of gastrointestinal disorders such as indigestion, lack of hunger, stomach pain, dysentery, diarrhea, constipation, and piles in western Nepal during different season of March 2020 to November 2020. The indigenous knowledge of local traditional healers having practical knowledge of plants in medicine was interviewed in 10 villages of Rupandehi district of western Nepal and native plants used for medicinal purposes were collected through questionnaire and personal interviews during fieldtrips. A total of 34 plant species belonging to 33 genera, and 27 families are documented in this study. The medicinal plants used in the treatment of gastrointestinal disorders by people are listed with botanical name (in binomial form), family, local names, habits, and parts used. This study showed that many people in the studied areas of Rupandehi district still continue to depend on the medicinal plants at least for the treatment of primary healthcare.